Implementasi Permainan Edukasi di Ruang Koleksi Anak sebagai Upaya Meningkatkan Kunjungan ke Ruang Anak Perpustakaan Proklamator Bung Hatta Bukittinggi - Saputri, Vadila Yulia; Marlini, Marlini; Rahmah, Elva (TSAQOFAH, 2026)
The development of library services requires innovations that can enhance children’s reading engagement and visits, one of which is the use of educational games in children’s collection rooms. Previous studies have shown that 3D educational games can improve early childhood literacy skills (Intisari et al., 2025), educational games encourage increased student visits to school libraries (Wulandari et al., 2025), and the integration of educational games into library services contributes to higher levels of children’s reading engagement (Patni et al., 2024). This study aimed to explain how educational games are used in the children’s collection room at Perpustakaan Proklamator Bung Hatta and the role of these games in increasing the number of children’s visits. The study employed a descriptive qualitative methodology with informants consisting of children’s room librarians and the head of the library services working team. Data were collected through observation, documentation, and interviews, and then analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that various types of educational games, such as puzzles, building blocks, Sudoku, logic games, and children’s crossword games, create a pleasant, interactive, and educational learning atmosphere for children, thereby increasing the frequency of visits to the children’s room and the duration of their visits to the library. However, the implementation of educational games also faced constraints, including the limited number of games, damage to materials due to intensive use, and insufficient supervision during peak hours. To address these constraints, librarians implemented strategies such as game rotation, routine maintenance, and clear rules of use for children. This study confirms that educational games function as an effective service innovation to increase children’s visits and engagement in the library, while offering practical implications for developing children’s room services through strengthening educational game collections and involving children in selecting types of games.